Multicolor Patterning of 2D Semiconductor Nanoplatelets - Khoshkhoo, Mahdi Samadi; Prudnikau, Anatol; Chashmejahanbin, Mohammad Reza; Helbig, Ralf; Lesnyak, Vladimir; Cuniberti, Gianaurelio (Giovanni) (ACS nano, 2021)
Nanocrystal micro/nanoarrays with multiplexed functionalities are of broad interest in the field of nanophotonics, cellular dynamics, and biosensing due to their tunable electrical and optical properties. This work focuses on the multicolor patterning of two-dimensional nanoplatelets (NPLs) via two sequential self-Assembly and direct electron-beam lithography steps. By using scanning electron microscopy, atomic force microscopy, and fluorescence microscopy, we demonstrate the successful fabrication of fluorescent nanoarrays with a thickness of only two or three monolayers (7-11 nm) and a feature line width of â 40 nm, which is three to four NPLs wide. To this end, first, large-Area thin films of red-emitting CdSe/ZnyCd1-yS and green-emitting CdSe1-xSx/ZnyCd1-yS core/shell NPLs are fabricated based on Langmuir-Type self-Assembly at the liquid/air interface. By varying the concentration of ligands in the subphase, we investigate the effect of interaction potential on the film's final characteristics to prepare thin superlattices suitable for the patterning step. Equipped with the ability to fabricate a uniform superlattice with a controlled thickness, we next perform nanopatterning on a thin film of NPLs utilizing a direct electron-beam lithography (EBL) technique. The effect of acceleration voltage, aperture size, and e-beam dosage on the nanopattern's resolution and fidelity is investigated for both of the presented NPLs. After successfully optimizing EBL parameters to fabricate single-color nanopatterns, we finally focus on fabricating multicolor patterns. The obtained micro/nanoarrays provide us with an innovative experimental platform to investigate biological interactions as well as Förster resonance energy transfer.
CRIS-Team Scopus Importer:2023-03-20
Keywords: colloidal semiconductor nanocrystals; core/shell nanoplatelets; electron-beam lithography; Langmuir-Type self-Assembly; nanopatterning